We-commerce: A study on Filipino consumers trading in a social context through online closed community groups (CCGs) - Jordan, Chiara Marie R. (Animo Repository, 2020)
With the rise of e-commerce, much innovation has taken place in various forms, be it the retailer websites, brand websites, or online shopping applications wherein the bulk of online trading transpires. However, it should be recognized that consumers may place value on other factors of which one or more of the aforementioned may or may not fall short on delivering, such as better deals or better trading terms. Thus, nothing is stopping consumers to still pursue online trading outside of these main platforms.An emerging form of online trading, nonetheless, is ‘Online Closed Community Groups’ (CCGs). Such seems to have affected the purchase behavior of particular groups of consumers and it is of the researchers’ interest to explore another e-commerce alternative that uniquely utilizes social media groups as marketplaces. Because dynamics may differ with other forms of ecommerce with trust, value, and prior online shopping or selling experience as potentially relevant factors, this study extends the Decomposed Theory of Planned Behavior (DTPB) by Taylor and Todd and explores the extent of the influence of its constructs to the behavioral intention of Filipinos in buying or selling in Online CCGs.373 respondents from the representative sample coming from Ateneo De Manila University (ADMU) and De La Salle University (DLSU) Online CCGs were surveyed online. Using SMART PLS for data analysis, statistical results show that the Perceived Usefulness and Ease of Use, Perceived Trust, Perceived Value, Compatibility, Interpersonal Influence, External Influence, Self-efficacy, Facilitating Conditions, Attitude, Subjective Norm, and Perceived Behavioral Control have a positive effect on the behavioral intention to transact in online CCGs (with pvalues < 0.05). Of these, Attitude is the most positively correlated with Intention. Furthermore, Perceived Trust (PT) is the most positively correlated with Attitude along with Compatibility (C), followed by Perceived Value (PV). On the theoretical contributions (PT and PV), findings suggest that even this online trading form without formal e-commerce infrastructure and security layers may thrive because trust in the particular community is present. As for value, supplementary findings contextualize that most respondents were buyers, and social feedback indicates that value gained may be monetary (bargains, the lower overall cost for acquiring an item) or not (ability to acquire an item only in the CCG). Meanwhile, the Frequency of Prior E-commerce Experience has no moderating effect on the relationship between Attitude and Intention, and this suggests that trial of this trading form may not be dependent on prior use of other e-commerce forms thus, hopefully making it worthy of further study. Moreover, this study may serve as an eye-opener for online retailers and Marketers that consumers in the Philippines can adapt to other retailing formats that do differ with what brands are used to, such as brand websites, retailer websites, and online shopping websites. May this be due to the country’s culture or heavy usage of social media, the social dimension of Online CCGs plays a big part concerning the researchers’ interest in pursuing this study. Globally, the dynamics and value-adding benefits of online community groups are just as worth exploring for brands especially those that wish to thrive, innovate, and trail blaze within a social target market. Equally, social media platforms may also find the results of this study of value as a starting point towards developing, rolling out, and testing relevant online shopping features.